Integrated Agricultural and Dairy Production within a Circular Economy Framework. A Comparison of Italian and Polish Farming Systems - Ghisellini, Patrizia; Protano, Gaetano; Viglia, Silvio; Gaworski, Marek; Setti, Marco; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
The livestock sector is required by the European Union policies to strengthen its multifunctional role by diversifying its production patterns. In Italy many dairy farms have already installed energy plants such as biogas digestors, mainly to increase their economic sustainability. We evaluate in this study the environmental performance of raw milk production to be used for world-renowned ParmigianoReggiano cheese production in a dairy farm located in northern Italy.Other products (crops, meat, biogas, electricity) are also included in the assessment. The study was carried out by means of Material Flow Accounting, Cumulative Energy Demand, Emergy Accounting and Life Cycle Assessment methods. The final purpose was to analyze the effects induced by different mixes of inputs (feedstock, electricity, fertilizers) and outputs (crops, milk, meat, electricity) on the process performance. The evaluation was implemented beforeand afterthe installation of a photovoltaic power plant and a biogas digester coupled to a biogas-fueled electric generator. This study explores five alternative scenarios: Scenario 1. An intensive livestock farm, in which feedstock and electricity are purchased from outside and manure is sold or disposed of; Scenario 2. The real farm before the implementation of PV and biogas, using a fraction of self-produced feedstock and manure as fertilizer; Scenario 3. The same farm, after photovoltaic electricity implementation, to cover 100% of local demand; Scenario 4. The same farm, after installing a manure digester and an electric generator, to produce electricity from biogas (sold as additional product, while digestate is used as fertilizer); 5. A Polish dairy farm, producing crops, meat and milk for the market, using manure as fertilizer and no renewable energy appliances. Results show local and large-scale improvements in the transition from Scenario 1 to Scenario 2 (due to increased optimization driven by fodder self-reliance) as well as in the transition from Scenario 3 to Scenario 3 (due to electricity self-reliance). The transition from Scenario 3 to Scenario 4 shows the added value of additional biogasdriven electric generation, while Scenario 5 shows the advantage of optimized milk production due to pedigree breeding, pasture availability and sale of crops in addition to dairy products. Results suggest that several kinds of improvements are possible by acting on farm structure, renewable energy supply, and different mix of products. Results also confirm the effectiveness of a multicriteriamultiscale biophysical assessment method towards a better understanding of costs and benefits of production alternatives.